2019
DOI: 10.1016/j.yjsbx.2019.100003
|View full text |Cite
|
Sign up to set email alerts
|

SmartBac, a new baculovirus system for large protein complex production

Abstract: A B S T R A C TRecent revolution of cryo-electron microscopy has opened a new door to solve high-resolution structures of macromolecule complexes without crystallization while how to efficiently obtain homogenous macromolecule complex sample is therefore becoming a bottleneck. Here we report SmartBac, an easy and versatile system for constructing large-sized transfer plasmids used to generate recombinant baculoviruses that express large multiprotein complexes in insect cells. The SmartBac system integrates the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 54 publications
0
16
0
1
Order By: Relevance
“…Here, the CATCHR domains of Sec5 and Sec8 of subcomplex I form large interfaces with subcomplex II, and Sec6 connects both subcomplexes like an arch. A preliminary 3D reconstruction of human exocyst from negatives stain EM yielded a particle of similar overall shape and size, suggesting that exocyst architecture is conserved …”
Section: Catchr Multisubunit Tethersmentioning
confidence: 99%
“…Here, the CATCHR domains of Sec5 and Sec8 of subcomplex I form large interfaces with subcomplex II, and Sec6 connects both subcomplexes like an arch. A preliminary 3D reconstruction of human exocyst from negatives stain EM yielded a particle of similar overall shape and size, suggesting that exocyst architecture is conserved …”
Section: Catchr Multisubunit Tethersmentioning
confidence: 99%
“…For the human MPC2, an additional EGFP (enhanced green fluorescent protein) tag was added before the His-tag. The use of the C-terminal EGFP tag was widespread for membrane proteins [ 49 , 50 ], including the purification of large multiprotein complexes [ 51 , 52 ], and was particularly useful in detecting inducible expression levels, solubility, stability, and the cellular compartmentalization of recombinant MPC [ 31 ].…”
Section: Contextual Discussionmentioning
confidence: 99%
“…This study found that cell lysis could be delayed and that recombinant protein yields could be increased by using cell lines constitutively expressing vankyrin or vankyrin-encoding baculovirus vectors (Steele et al, 2017). SmartBac, a new baculovirus system, was developed for large protein complex production (Zhai et al, 2019). The FlexiBAC protein expression system was also developed for the production of both cytosolic proteins and secreted proteins that require proteolytic maturation.…”
Section: Insect Cellsmentioning
confidence: 99%